PENGARUH PENDAPATAN, JUMLAH NASABAH DAN HARGA EMAS TERHADAP PENYALURAN PEMBIAYAAN RAHN PADA PT. PEGADAIAN SYARIAH UPS PASAR ANGSO DUO JAMBI (PERIODE 2015-2022) - Nur fadilah; Addiarrahman Addiarrahman; Solichah Solichah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study is to find out the influence of income, number of customers and gold price on the distribution of PT's rahn financing. Sharia Pawn UPS Pasar Angso Duo Jambi (Season 2015-2022). The research method used in this study is a quantitative method. The independent variables used in this study are income, number of customers and price of gold. The dependent variable is the distribution of stone financing. Data obtained from secondary and primary data. The statistical mode uses multiple linear regression analysis, t-test, f-test and coefficient determination analysis.The results of this study show that income (X1) has a significant effect on the distribution of Rahn funding, as the significance value obtained is 0.002 and 0.05. This means that the income variable affects the distribution of lump sum funding. The number of customers (X2) has a significant impact on the distribution of the amount of funding, because the resulting significance value is 0.000andlt;0.05. And the price of gold (X3) significantly affects the distribution of the funding of the rock, because the resulting significance value is 0.037 andlt; 0.05. Judging by the simultaneous income test, the number of customers and the price of gold together affect the distribution of lump sum financing in PT. sharia pawn shop ups angso duo market jambi.